2017
DOI: 10.1016/j.micres.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and metabolic traits endow Bacillus velezensis CC09 with a potential biocontrol agent in control of wheat powdery mildew disease

Abstract: Bacillus velezensis CC09, which was isolated from healthy leaves of Cinnamomum camphora and previously identified as Bacillus amyloliquefaciens CC09, shows great potential as a new biocontrol agent, in control of many phytopathogenic diseases. To extend our understanding of the potential antifungal capacities, we did a whole genome analysis of strain CC09. Result shows that strain CC09 has a relatively large genome size (4.17Mb) with an average GC content of 46.1%, and 4021 predicted genes. Thirteen secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 41 publications
1
49
0
1
Order By: Relevance
“…This strain can also synthesize antifungal compounds, such as fengycin, bacillomycin D, difficidin, bacilysin, and amylocyclicin [34]. B. velezensis has been used in the biocontrol of both wheat, powdery mildew by Blumeria granminis and Wilt Disease Fusarium oxysporium [35]. Recently, Cheng et al (2019) reported that B. methylotrophicus showed efficacy on the management of Maize stalk rot [36].…”
Section: Evaluation Of Phytophthora Antagonism In Greenhouse By Endopmentioning
confidence: 99%
“…This strain can also synthesize antifungal compounds, such as fengycin, bacillomycin D, difficidin, bacilysin, and amylocyclicin [34]. B. velezensis has been used in the biocontrol of both wheat, powdery mildew by Blumeria granminis and Wilt Disease Fusarium oxysporium [35]. Recently, Cheng et al (2019) reported that B. methylotrophicus showed efficacy on the management of Maize stalk rot [36].…”
Section: Evaluation Of Phytophthora Antagonism In Greenhouse By Endopmentioning
confidence: 99%
“…irteen secondary metabolite clusters were [22]. Several productions of antimicrobial-volatile compounds, acetoin, and 2-butanone can also be produced by B. velezensis or B. subtilis [23].…”
Section: Resultsmentioning
confidence: 99%
“…plantarum and B. oryzicola have been shown to be conspecific by recent phylogenetic analysis (Dunlap, Kim, Kwon, & Rooney, ). Many strains of B. velezensis have been reported as antagonists of plant pathogens (Cai, Liu, Wang, & Xue, ; Chen et al, ; Palazzini, Dunlap, Bowman, & Chulze, ). Similarly, a broad inhibitory spectrum was detected in the LYLB4 strain.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focused on finding microorganisms that occur naturally on pears to control the postharvest pathogens that affect pear fruits. The bacterial LYLB4 strain, isolated from pear fruits, was selected for further study because of its strong inhibi- (Cai, Liu, Wang, & Xue, 2017;Chen et al, 2009;Palazzini, Dunlap, Bowman, & Chulze, 2016). Similarly, a broad inhibitory spectrum was detected in the LYLB4 strain.…”
Section: Discussionmentioning
confidence: 99%